2017
DOI: 10.1080/13102818.2017.1334592
|View full text |Cite
|
Sign up to set email alerts
|

Plasma endothelin-1 and endothelin-A receptor concentrations in patients with primary open-angle glaucoma

Abstract: Endothelin-1 (ET-1) is a potent vasoconstrictor and is considered to have a key role in the regulation of ocular perfusion and glaucoma pathogenesis. High ET-1 and ET A -receptor levels are reported in patients with primary open-angle glaucoma (POAG). We compared the mean plasma ET-1 and ET Areceptor concentration of controls and patients with early and advanced POAG stage, and assessed the correlation with the retinal nerve fibre layer (RNFL) thickness. The study included a total of 75 participants, aged 45-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 24 publications
1
12
1
Order By: Relevance
“…Our results are confirmed by the study by Савина (14,17,18) which identifies the occurrence of post-stroke GTR, the presence of depression in the acute period of stroke, and its tense course is determined by social factorspresence of social connections at the time of the stroke (). According to a study by Burvill et.…”
Section: Figure 10 Correlation Between the Severity Of Depression Ansupporting
confidence: 86%
“…Our results are confirmed by the study by Савина (14,17,18) which identifies the occurrence of post-stroke GTR, the presence of depression in the acute period of stroke, and its tense course is determined by social factorspresence of social connections at the time of the stroke (). According to a study by Burvill et.…”
Section: Figure 10 Correlation Between the Severity Of Depression Ansupporting
confidence: 86%
“…In the control group, the mean ET-1 plasma level was 4.88 ± 1.75 pg/mL, whereas in the patients with early glaucoma stage, it was 6.33 ± 2.38 pg/mL, and in the advanced glaucoma patients, 6.34 ± 1.56 pg/mL. We [27] found a statistically significant difference in the ET-1 plasma concentration between the controls and the early glaucoma patients (p ¼ 0.029), the control group and the advanced glaucoma patients (p ¼ 0.018), but we could not find significant difference between the two glaucoma groups (p ¼ 0.998) after application of inter-group comparative analysis. Therefore, it could be suggested that the increase in the ET-1 level may be related with the glaucoma development and may play a role in the pathogenesis of the disease.…”
Section: Resultsmentioning
confidence: 59%
“…In the study of Estrom et al (9), 60% of the patients with early depression recover in one year. Similarly, according to a study by Burvill et al (10), 41% of the patients who were depressed 4 months after stroke remained depressed in the next 12 months as well. Based on the results of Estrom et al (9), there appears to be a high risk of chronic depression if the patient did not recover in the first year after the stroke.…”
Section: Introductionmentioning
confidence: 76%
“…The physical impairment and depression, are the link between neuropsychological sequelae and other diseases (11,12). For many years, only the psychogenic response to the disability was believed to be the major cause of post-stroke depression (10). Subsequently, psychosocial factors have begun to attach some importance to endogenous factors (individual personality and hereditary predisposition) (13).…”
Section: Introductionmentioning
confidence: 99%